Anemia in pregnancy at two levels of health care in Ibadan, south west Nigeria (2011)
Background: In Africa, anemia in pregnancy contributes to non-attainment of the MDG goals 4 and 5. This study examined the prevalence and some risk factors for anemia at two levels of health care in the Ibadan metropolis. Methods: This was a retrospective study of the booking records of pregnant women at the University College Hospital (UCH, a profit-making tertiary institution) and Adeoyo Maternity Hospital (AMH, a secondary level institution offering free services) in Ibadan, September 1, 2008 to December 31, 2008. Eligible women had singleton pregnancies and no known chronic illnesses. Anemia was defined as packed cell volume (PCV) <30%, and degrees of anemia as mild (PCV 27–29%), moderate (PCV 19–26%), and severe (PCV below 19%). Statistical analysis was done by the Chi-square test, Fisher exact test, and t-test. A P value of <0.05 was considered significant. Results: Data from 2702 women (384 and 2318 from UCH and AMH, respectively) were available for analysis. About 30% of the women were anemic. The patients in UCH had higher mean PCV (33.03± 4.32 vs. 31. 04 ± 4.09, P = 0.00). A higher proportion of anemia was seen in patients presenting in Adeoyo (32.4% vs. 16.7%, P = 0.00). Factors associated with anemia included young age (P = 0.00), low parity (P = 0.00), and hospital type (P = 0.00). Parity and hospital type remained significant on logistic regression. Conclusion: Lower prevalence of anemia at the tertiary hospital maybe attributed to the higher socioeconomic status of the clientele. Short-term early antenatal management of anemia and long-term economic/educational empowerment is advocated.